Frequency of shedding of respiratory pathogens in horses recently imported to the United States. (15th May 2018) - Smith, Fauna Leah; Watson, Johanna L.; Spier, Sharon J.; Kilcoyne, Isabelle; Mapes, Samantha; Sonder, Claudia; Pusterla, Nicola
Abstract : Background: Imported horses that have undergone recent long distance transport might represent a serious risk for spreading infectious respiratory pathogens into populations of horses. Objective: To investigate the frequency of shedding of respiratory pathogens in recently imported horses. Animals: All imported horses with signed owner consent (n = 167) entering a USDA quarantine for contagious equine metritis from October 2014 to June 2016 were enrolled in the study. Methods: Prospective observational study. Enrolled horses had a physical examination performed and nasal secretions collected at the time of entry and subsequently if any horse developed signs of respiratory disease during quarantine. Samples were assayed for equine influenza virus (EIV), equine herpesvirus type‐1, −2, −4, and −5 (EHV‐1, −2, −4, −5), equine rhinitis virus A (ERAV), and B (ERBV) and Streptococcus equi subspecies equi ( S. equi) using quantitative PCR (qPCR). Results: Equine herpesviruses were detected by qPCR in 52% of the study horses including EHV‐2 (28.7%), EHV‐5 (40.7%), EHV‐1 (1.2%), and EHV‐4 (3.0%). Clinical signs were not correlated with being qPCR‐positive for EHV‐4, EHV‐2, or EHV‐5. None of the samples were qPCR‐positive for EIV, ERAV, ERBV, and S. equi . The qPCR assay failed quality control for RNA viruses in 25% (46/167) of samples. Conclusions and Clinical Importance: Clinical signs of respiratory disease were poorly correlated with qPCR positive status for EHV‐2, −4, and −5. The importance of γ ‐ herpesviruses (EHV‐2 and 5) in respiratory disease is poorly understood. Equine herpesvirus type‐1 or 4 (EHV‐1 or EHV‐4) were detected in 4.2% of horses, which could have serious consequences if shedding animals entered a population of susceptible horses. Biosecurity measures are important when introducing recently imported horses into resident US populations of horses.